Findings of quality management studies in primary and secondary education: a systematic literature review. Issue 3 (23rd September 2020) - Bouranta, Nancy; Psomas, Evangelos; Antony, Jiju
Abstract : Purpose: The aim of this paper is to present the main findings of the studies in the field of quality management (QM) in primary and secondary education. Grouping these findings into themes and these themes, in turn, into broad categories as well as prioritizing the themes of findings are also aims of the present study. Design/methodology/approach: A systematic literature review (SLR) of articles focusing on QM in primary and secondary education was carried out based on major publishers, namely Emerald Online, Taylor and Francis, Elsevier/Science Direct, Springer Link, Sage Publishing and Online. In total, 133 articles published in 62 journals during 1983–2019 were collected. The affinity diagram was applied in order to group the findings of the QM studies into logical themes and these themes into broad categories. Moreover, the Pareto diagram was applied to prioritize the themes revealed. Findings: A plethora of articles focusing on QM in primary and secondary education have been published in the last decades. The findings of the QM studies presented in the 133 reviewed articles are grouped into 43 themes and these themes, in turn, into 6 broad categories, namely management practices, school characteristics, teachers, stakeholders, government and pupils. The analysis also reveals themes that can be characterized as "vital" and "useful." Practical implications: Researchers and school managers can take into consideration the findings of the QM studies in primary and secondary education as well as the themes of high priority for the design of future studies and QM implementation plans, respectively. Originality/value: This is the first literature review study which presents analytically the findings of the QM studies in primary and secondary education. This study also contributes to the literature by formulating meaningful themes of these findings and broad categories of these themes and by prioritizing the themes revealed.